What is causing the Black fungus menace? - Bhattacharya, Ambarish; Ghosh, Kaushik (Asian Journal of Medical Sciences, 2021)
Even with the weaning of second wave of covid 19 epidemic the cases of Mucormycosis or black fungus, a rare but potentially life-threatening condition is on rise. By the order of central health ministry all states have put it in the list of notifiable disease under the Epidemic Diseases Act, 1897. This sudden familiarization of the term black fungus both in media as well as in literature has causes a huge outcry and phobia in most certain terms. This is not only unjustified in most instances and added flavor to already panic-stricken minds of common people. We are noticing an effort of overnight infrastructure building as well as a rising demand for a superspeciality set up by ignoring the very basic needs of our overburden health care sector. Here we have tried to share our perspective regarding this menace by searching the facts and myths and suggested hypothesizes.